A composite binary lithium supplement material and preparation method thereof

By combining Li2O and Li3N and carbon coating treatment, composite binary lithium supplement material was prepared, which solved the reduction in energy utilization rate of lithium-ion batteries during the first charge and the high decomposition voltage of pre-lithium materials and alkaline properties of the pre-lithium materials. The problem of high and air instability has achieved high energy density and long cycle life.

CN118888758BActive Publication Date: 2025-02-07ZIJIN MINING RENEWABLE ENERGY & ADVANCED MATERIALS (CHANGSHA) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411366641.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-07
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

During the first charging of existing lithium-ion batteries, the formation of CEI film and SEI film, the shedding of active materials and the irreversible deposition of lithium metal, resulting in a decrease in battery energy utilization, and the commonly used preliminaries such as Li2O and Li3N have a high decomposition voltage. , high alkalinity and unstable air problems affect the cycle life and energy density of the battery.

Method used

By combining Li2O and Li3N, using PECVD vacuum air atmosphere equipment for one-step in-situ synthesis, then reacting with high-purity nitrogen, and finally carbon coating was performed through plasma vapor deposition technology to prepare a composite binary lithium supplement material xLi2O- yLi3N-zC@C.

Benefits of technology

The theoretical decomposition potential of Li2O is reduced, the lithium ion conductivity is improved, the electronic conductivity of the material is enhanced, the sensitivity to moisture and carbon dioxide in the air is reduced, and the specific capacity and cycle stability of the composite material are improved for the first charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888758B_ABST
    Figure CN118888758B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of lithium supplementation technology, and in particular to a composite binary lithium supplementation material and a preparation method thereof. The preparation method of the composite binary lithium supplementation material provided by the present invention comprises the following steps: 1) mixing a lithium source and a carbon source, reacting them in a PECVD vacuum atmosphere device at a first temperature to obtain a composite A; 2) lowering the first temperature to a second temperature, introducing nitrogen gas to allow the composite A to react with nitrogen gas to obtain a composite B; 3) raising the second temperature to a third temperature, introducing gas to coat the composite B with a carbon layer to obtain a composite binary lithium supplementation material. The present invention mixes Li 2 O and Li 3 N is used in combination, and the composite material is carbon-coated to reduce Li 2 O's theoretical decomposition potential, improving the comprehensive charge-to-gram capacity, while reducing its sensitivity to moisture and carbon dioxide in the air and reducing its demanding usage conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium supplementation, and in particular to a composite binary lithium supplementation material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have advantages such as high energy density and long cycle life, and are widely used in consumer electronics, power batteries, energy storage and other fields. However, when lithium-ion batteries are charged for the first time, the formation of CEI film and SEI film, the shedding of active materials on the negative electrode side and the irreversible deposition of lithium metal will inevitably occur, which consumes part of the active lithium ions from the positive electrode material, causing the battery's available energy to decrease. Positive electrode "pre-lithiation" is to add additional pre-lithium materials to the positive electrode before the lithium-ion battery works to replenish lithium ions. Pre-lithiation replenishes lithium to the electrode material to offset the irreversible lithium loss caused by the CEI film and SEI film, thereby improving the battery's cycle life and energy density.

[0003] At present, the types of positive electrode pre-lithium materials commonly used in this field include Li5FeO4, Li2NiO2, Li2C2O4, Li6CoO4, Li2CuO2, and Li2O. The theoretical capacity of binary lithium compounds (such as Li2O, LiF, and Li3N) is much higher than that of lithium-rich compounds and other sacrificial lithium salts. They have the advantages of good compatibility with battery systems, non-toxicity, high gram capacity, and relatively simple synthesis process. Li2O has a high theoretical specific capacity (1794 mAh / g), but lithium oxide has an inverse fluorite structure and its lithium ion conductivity is low. The use of Li2O must overcome two challenges: 1) Its high decomposition voltage (>4.7 V vs.Li + / Li) usually faces the risk of electrolyte decomposition; 2) its high alkalinity will attack the PVDF in the positive electrode slurry, causing the slurry to lose viscosity; 3) it is unstable in the air and easily reacts with water and carbon dioxide. Li3N is an attractive theoretical specific capacity (2309 mAh / g). It is a layered lithium ion conductor with high lithium ion conductivity and low theoretical decomposition potential (~0.44 V vs.Li + / Li). However, the utilization of Li3N must overcome two challenges: 1) it is incompatible with N-methylpyrrolidone (NMP) solvent widely used in conventional battery slurry processes; 2) its intrinsic electronic conductivity is low; 3) it has high chemical reactivity to humidity in the ambient atmosphere. Li2O and Li3N each have their own advantages and disadvantages.

[0004] The paper "Enabling high energy density Li-ion batteries through Li2Oactivation" (Nano Energy, 2016, 27: 196-201.) reports that lithium oxide is activated in the presence of layered composite cathode materials (HEM), significantly increasing the energy density of lithium-ion batteries. The degree of activation depends on the current rate, electrolyte salt and anode type. In full battery tests, lithium oxide was used as a lithium source to combat the first cycle irreversibility of high-capacity composite alloy anodes. When lithium oxide was mixed with HEM as a cathode, the electrochemical performance was improved in a full battery with SiO-SnCoC composites as anodes. The mechanism behind lithium oxide activation can also explain the first charge platform and the abnormally high capacity associated with these high-energy cathode materials. Although it has a high theoretical pre-lithiation capacity during charging, the problem of lithium oxide air stability is not solved. The document "Stabilized Li3N for Efficient Battery Cathode Prelithiation" (Energy Storage Materials, 2017, 6: 119-124.) reports a simple method for preparing surface passivated Li3N material. Metallic lithium reacts with nitrogen and then performs annealing to prepare surface passivated Li3N material. The dense surface passivation layer composed of crystalline Li2O and Li2CO3 isolates the active components of the material from the air, thereby achieving good stability. However, its passivated surface is composed of crystalline Li2O and Li2CO3, and Li2O and Li2CO3 will increase the residual alkali of the material, which is not conducive to the preparation of battery slurry. At the same time, the electronic conductivity of Li3N is low, which affects its gram-to-gram capacity. Invention CN 115650263 A provides a method for preparing battery-grade lithium oxide. The method is to add lithium hydroxide monohydrate to hydrogen peroxide at room temperature for a synthesis reaction, the synthesis reaction is first stirred at a low temperature of less than 45°C, and then heated to a high temperature of 95-100°C for a stirring reaction, solid-liquid separation to obtain low-water content lithium peroxide; vacuum drying and dehydration at 0-95°C to obtain lithium peroxide, which is heated and thermally decomposed in a vacuum furnace to obtain a battery-grade lithium oxide powder product, but its preparation method is complicated, the process safety is low, and the related defects of lithium oxide as a lithium supplement have not been solved. The existing technology is still imperfect in solving the above problems. At present, there is an urgent need to provide a new composite binary lithium supplement material and a preparation method. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a composite binary lithium supplement material and a preparation method thereof.

[0006] Specifically, the method for preparing the composite binary lithium supplement material provided in the first aspect of the present invention comprises the following steps.

[0007] 1) A lithium source and a carbon source are mixed and reacted in a PECVD vacuum atmosphere device at a first temperature to obtain a composite A.

[0008] 2) lowering the temperature from the first temperature to a second temperature, introducing nitrogen gas to allow the compound A to react with the nitrogen gas to obtain a compound B.

[0009] 3) The temperature is raised from the second temperature to a third temperature, and a gas is introduced to coat the composite B with a carbon layer to obtain a composite binary lithium supplement material.

[0010] In the present invention, Li2O and Li3N are used in combination by the above method, thereby reducing the theoretical decomposition potential of Li2O, and coating the composite material at the same time, further improving the comprehensive charge gram specific capacity while reducing its sensitivity to moisture and carbon dioxide in the air, and reducing its harsh use conditions. Moreover, the preparation method of the composite binary lithium supplement material provided by the present invention realizes the one-step in-situ synthesis of Li2O-Li-carbon composites by step one, and realizes the reaction of Li2O-Li-carbon composites with high-purity nitrogen by step two to obtain Li2O-Li3N-carbon composites, and further realizes carbon coating of Li2O-Li3N-carbon composites by plasma vapor deposition technology by step three. The carbon coating temperature of the PECVD vacuum atmosphere furnace is lower than that of the CVD atmosphere furnace, which can avoid the thermal decomposition of Li3N caused by high-temperature carbon coating. During the entire preparation process from step one to step three, the raw materials and reaction intermediates are always processed in a PECVD vacuum atmosphere furnace, which not only reduces the equipment processing cost and improves the overall preparation efficiency, but also avoids the impact of the environment caused by the intermediate conversion atmosphere furnace on the performance of the composite binary lithium supplement material.

[0011] Preferably, in step 1), the carbon source is selected from one or more of glucose, sucrose, citric acid, carbon black and lithium carbide.

[0012] Preferably, the carbon source is lithium carbide and / or carbon black.

[0013] Preferably, in step 1), the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium acetate and lithium carbide.

[0014] Preferably, the lithium source is lithium oxide and / or lithium hydroxide.

[0015] In the present invention, lithium carbide and / or carbon black, lithium oxide and / or lithium hydroxide are preferably used as raw materials so that the first charge gram-specific capacity of the prepared composite binary lithium supplement material is further improved.

[0016] Further preferably, in step 1), the molar ratio of all lithium to carbon in the lithium source and the carbon source is (1-0.1): (0.1-1).

[0017] Preferably, the molar ratio of all lithium to carbon in the lithium source and the carbon source is (0.8-0.2): (0.2-0.8).

[0018] More preferably, in step 1), the vacuum atmosphere pressure is 10-100 Pa.

[0019] Preferably, the vacuum atmosphere pressure is 10~50Pa.

[0020] Further preferably, in step 1), the heating program of the first temperature is: heating to 500-600°C at a heating rate of 2-10°C / min, keeping warm for 2-5h, and then heating to 800-1000°C, keeping warm for 1-5h.

[0021] Preferably, the heating program of the first temperature is: heating to 550-600°C at a heating rate of 2-5°C / min, keeping warm for 2-3h, and then heating to 900-1000°C, keeping warm for 2-5h.

[0022] Further preferably, in step 2), during the sintering process, the second temperature is 200-400° C., the cooling rate is 2-10° C. / min, and the holding time is 5-30 h.

[0023] Preferably, the second temperature is 200-300° C., the cooling rate is 2-5° C. / min, and the holding time is 10-25 h.

[0024] Further preferably, in step 3), during the carbon layer coating process, the third temperature is 400-700° C., and the reaction time is 0.5-5 h.

[0025] Preferably, the third temperature is 450-600° C., and the reaction time is 0.5-3 h.

[0026] Further preferably, in step 3), during the carbon layer coating process, the plasma chemical vapor deposition procedure is: after the second temperature is raised to the third temperature at a rate of 2°C / min, gas is introduced into the atmosphere furnace, and after being kept at the third temperature for a period of time, it is naturally cooled to room temperature to obtain a carbon layer-coated composite binary lithium supplement material.

[0027] Preferably, in step 3), during the carbon layer coating process, the gas is selected from one or more of high-purity methane, ethane, propane, butane, ethylene, propylene, butene, pentene, acetylene, propyne and butyne.

[0028] And / or, in step 3), during the carbon layer coating process, the carbon coating amount on the surface of the composite binary lithium supplementing material accounts for 0.5%~5%; preferably, the carbon coating amount accounts for 1.5%~3%.

[0029] More preferably, the gas used is a high-purity gas with a purity ≥ 99.999%.

[0030] Further preferably, the preparation method of the present invention is carried out under the protection of an inert gas, preferably nitrogen or argon.

[0031] The composite binary lithium supplement material prepared by the present invention, the xLi2O-yLi3N-zC@C material, uses Li3N with high energy density, high lithium ion conductivity and low decomposition potential to be combined with Li2O, which not only improves the lithium ion conductivity of Li2O, but also reduces the decomposition potential of Li2O. At the same time, the amorphous carbon network penetrates the internal structure of Li2O and Li3N, improves the electronic conductivity of Li3N and Li2O, and reduces the high decomposition voltage of Li2O (>4.7 V vs.Li + / Li) leading to the risk of electrolyte failure.

[0032] The second aspect of the present invention provides a composite binary lithium-supplementing material prepared by the preparation method of the composite binary lithium-supplementing material, and the chemical formula of the composite binary lithium-supplementing material is: xLi2O-yLi3N-zC@C; x+y+z=1, 0.1≤x≤0.9, 0.1≤y≤0.9, 0.01≤z≤0.2.

[0033] Preferably, the surface of the composite binary lithium-supplementing material is uniformly coated with a carbon coating layer of a conductive carbon material, and the thickness of the carbon coating layer is preferably 0.5-200 nm.

[0034] In the present invention, Li2O has a strong alkalinity and has the problem of destroying the viscosity of PVDF in the positive electrode slurry of the lithium-ion battery. Li3N is incompatible with NMP in the positive electrode slurry of the lithium-ion battery. The internal network penetration mode of amorphous carbon and the surface carbon coating structure are adopted to avoid direct contact between Li2O and Li3N and the battery slurry, prevent the occurrence of side reactions, and at the same time, PECVD carbon coating increases the stability of the composite binary lithium supplement material in the air.

[0035] The beneficial effect of the present invention is at least that: the present invention uses Li2O and Li3N in combination, thereby reducing the theoretical decomposition potential of Li2O, and at the same time, the composite material is coated to reduce its sensitivity to moisture and carbon dioxide in the air, thereby reducing its harsh use conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. It is obvious that the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is the X-ray diffraction pattern of the composite binary lithium material-1 obtained in Example 1 of the present invention.

[0038] Figure 2 This is a SEM image of the surface carbon coating of the composite binary lithium material-1 obtained in Example 1 of the present invention.

[0039] Figure 3 This is the X-ray diffraction pattern of lithium oxide-1 obtained in Comparative Example 2 of the present invention.

[0040] Figure 4 This is the X-ray diffraction pattern of lithium nitride-1 in comparative example 3 of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0043] If no specific technology or conditions are specified in the examples of the present invention, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The experimental reagents and raw materials involved are all commercially available, and the reagents are all analytically pure products.

[0044] In the following examples, the main experimental equipment involved are: 1) high-energy ball mill pulverisette 7 premiumline; 2) ion enhanced chemical vapor deposition rotary tube furnace OTF-1200X-III-R5-PECVD (the experiment is carried out under the protection of an inert gas, preferably nitrogen or argon).

[0045] Example 1

[0046] (1) Lithium hydroxide and lithium carbide were weighed according to a lithium:carbon molar ratio of 0.6:0.4, respectively, and after being uniformly mixed by ball milling, they were transferred to a PECVD vacuum atmosphere furnace. Under a vacuum atmosphere of 50 Pa, the first temperature control program was set: the temperature was increased from room temperature to 550°C at a heating rate of 2°C / min, kept at this temperature for 2 h, and then increased to 850°C and kept at this temperature for 5 h to obtain composite A.

[0047] (2) After the above reaction is completed, set the second temperature control program: cool the PECVD vacuum atmosphere furnace from 550°C to 300°C at a cooling rate of 10°C / min, introduce high-purity nitrogen, and keep the temperature at 300°C for 12 h. Composite A reacts with nitrogen to obtain composite B.

[0048] (3) After the above reaction is completed, a plasma enhanced chemical vapor deposition program is set up: the temperature is raised from 300°C to 500°C at a rate of 2°C / min, high-purity methane gas is introduced into the atmosphere furnace, and the mixture is kept at 500°C for 3 hours and then naturally cooled to room temperature. Under this program, the above composite B is carbon-coated, and then the composite binary lithium material-1 is obtained by screening and demagnetization. The carbon coating accounts for 3.0%. The residual alkali content of the finished product is tested, and the residual alkali content of the finished product is shown in Table 1. The residual alkali content refers to the content of alkaline substances (LiOH+Li2CO3) remaining on the surface of the positive electrode lithium supplement.

[0049] The composite binary lithium material-1 prepared in this embodiment has the chemical formula: 0.5Li2O-0.4Li3N-0.1C@C; x=0.5, y=0.4, z=0.1. The surface of the composite binary lithium supplement material is uniformly coated with a carbon coating layer of conductive carbon material, and the thickness of the carbon coating layer is 200nm.

[0050] The finished product was characterized by XRD and SEM, and the results were as follows: Figure 1-2 .from Figure 1 The XRD pattern analysis shows that the diffraction peaks of the composite binary lithium supplement material are composed of Li2O and Li3N phases. Figure 2 The SEM image analysis showed that the surface of the composite binary lithium supplement material was evenly carbon-coated and the sample was a black powdery solid. Therefore, this method was used to prepare a composite binary lithium supplement material.

[0051] Example 2

[0052] (1) Lithium oxide and carbon black were weighed according to a lithium to carbon molar ratio of 0.7:0.3, and were mixed uniformly by ball milling. The mixture was then transferred to a PECVD vacuum furnace. Under a vacuum atmosphere of 40 Pa, the first temperature control program was set: the temperature was increased from room temperature to 500°C at a heating rate of 2°C / min, and the mixture was kept at this temperature for 2 h. The temperature was then increased to 950°C and the mixture was kept at this temperature for 2 h to obtain composite A.

[0053] (2) After the above reaction is completed, set the second temperature control program: cool the PECVD vacuum atmosphere furnace from 550°C to 260°C at a cooling rate of 5°C / min, introduce high-purity nitrogen, and keep the temperature at 260°C for 14 h. Composite A reacts with nitrogen to obtain composite B.

[0054] (3) After the above reaction is completed, a plasma enhanced chemical vapor deposition program is set: the temperature is raised from 260°C to 550°C at a rate of 2°C / min, high-purity acetylene gas is introduced into the atmosphere furnace, and the temperature is kept at 550°C for 0.5h and then naturally cooled to room temperature. Under this program, the above-mentioned composite B is carbon-coated, and then the composite binary lithium material-2 is obtained by screening and demagnetization. The carbon coating ratio is 0.5%. The finished product is tested for residual alkali content. The residual alkali content of the finished product is shown in Table 1. The composite binary lithium material-2 prepared in this embodiment has a chemical formula of 0.3Li2O-0.6Li3N-0.1C@C; x=0.3, y=0.6, z=0.1. The surface of the composite binary lithium supplement material is uniformly coated with a carbon coating layer of conductive carbon material, and the thickness of the carbon coating layer is 20nm.

[0055] Example 3

[0056] This example is carried out in a similar manner to that of Example 2, except that in step (1), the molar ratio of lithium to carbon used in this example is 0.8:0.2.

[0057] The composite binary lithium material-3 was prepared, and the residual alkali content of the finished product was tested. The residual alkali content of the finished product is shown in Table 1.

[0058] The composite binary lithium material-3 prepared in this embodiment has a carbon coating ratio of 0.5%, and the chemical formula is: 0.2Li2O-0.6Li3N-0.2C@C; x=0.2, y=0.6, z=0.2. The surface of the composite binary lithium supplement material is uniformly coated with a carbon coating layer of conductive carbon material, and the thickness of the carbon coating layer is 25nm.

[0059] Example 4

[0060] (1) Lithium oxide and lithium carbide were weighed according to a lithium:carbon molar ratio of 0.5:0.5, respectively, and mixed evenly by ball milling. The mixture was then transferred to a PECVD vacuum furnace. Under a vacuum atmosphere of 10 Pa, the first temperature control program was set: the temperature was increased from room temperature to 600°C at a heating rate of 3°C / min, and the mixture was kept at this temperature for 3 h. The temperature was then increased to 950°C and kept at this temperature for 4 h to obtain composite A.

[0061] (2) After the above reaction is completed, set the second temperature control program: cool the PECVD vacuum atmosphere furnace from 550°C to 250°C at a cooling rate of 3°C / min, introduce high-purity nitrogen, and keep the temperature at 250°C for 18 hours. Compound A reacts with nitrogen to obtain compound B.

[0062] (3) After the above reaction is completed, set up a plasma enhanced chemical vapor deposition program: heat up from 250°C to 500°C at a rate of 2°C / min, introduce high-purity acetylene gas into the atmosphere furnace, keep warm at 500°C for 2h and then cool naturally to room temperature. Under this program, the above-mentioned composite B is carbon-coated, and then screened and demagnetized to obtain composite binary lithium material-4, with a carbon coating ratio of 2.0%. The residual alkali content of the finished product is tested, and the residual alkali content of the finished product is shown in Table 1. Among them, the residual alkali content refers to the content of alkaline substances (LiOH+Li2CO3) remaining on the surface of the positive electrode lithium supplement.

[0063] The composite binary lithium material-4 prepared in this embodiment has the chemical formula: 0.2Li2O-0.75Li3N-0.05C@C; x=0.2, y=0.75, z=0.05. The surface of the composite binary lithium supplement material is uniformly coated with a carbon coating layer of conductive carbon material, and the thickness of the carbon coating layer is 60nm.

[0064] Example 5

[0065] This example is carried out in a similar manner to that of Example 4, except that in step (1), lithium acetate, lithium carbide, glucose, and sucrose are weighed in a lithium to carbon element molar ratio of 0.5:0.5.

[0066] The composite binary lithium material-5 was prepared, and the residual alkali content of the finished product was tested. The residual alkali content of the finished product is shown in Table 1.

[0067] Example 6

[0068] Lithium acetate, lithium carbide, glucose and sucrose were weighed according to a lithium:carbon molar ratio of 0.5:0.5, respectively, and mixed evenly by ball milling at high speed. Then, the mixture was transferred to a PECVD vacuum atmosphere furnace. Under a vacuum atmosphere of 50 Pa, the first temperature control program was set: the temperature was increased from room temperature to 500°C at a heating rate of 10°C / min, kept at this temperature for 5 h, and then increased to 800°C and kept at this temperature for 5 h to obtain composite A.

[0069] After the above reaction is completed, set the second temperature control program: according to the cooling rate of 3°C / min, the PECVD vacuum atmosphere furnace is cooled from 550°C to 200°C, and then high-purity nitrogen is introduced and kept at 200°C for 25h. Compound A reacts with nitrogen to obtain compound B.

[0070] (3) After the above reaction is completed, set up a plasma enhanced chemical vapor deposition program: heat from 200°C to 400°C at a rate of 2°C / min, introduce high-purity acetylene gas into the atmosphere furnace, keep warm at 400°C for 5 hours and then cool naturally to room temperature. Under this program, the above-mentioned composite B is carbon-coated, and then screened and demagnetized to obtain composite binary lithium material-6, with a carbon coating ratio of 5.0%. The residual alkali content of the finished product is tested, and the residual alkali content of the finished product is shown in Table 1. Among them, the residual alkali content refers to the content of alkaline substances (LiOH+Li2CO3) remaining on the surface of the positive electrode lithium supplement.

[0071] The composite binary lithium material-6 prepared in this embodiment has the chemical formula: 0.8Li2O-0.15Li3N-0.05C@C; x=0.8, y=0.15, z=0.05. The surface of the composite binary lithium supplement material is uniformly coated with a carbon coating layer of conductive carbon material, and the thickness of the carbon coating layer is 200nm.

[0072] Comparative Example 1

[0073] This example is carried out in a similar manner to Example 2, except that the carbon coating step is not performed in this comparative example, that is, step (3) is not performed.

[0074] A composite binary lithium material-7 was prepared, with the chemical formula: 0.3Li2O-0.6Li3N-0.1C; x=0.3, y=0.6, z=0.1. The residual alkali content of the finished product was tested, and the residual alkali content of the finished product is shown in Table 1.

[0075] Comparative Example 2

[0076] Synthesis of pure phase lithium oxide.

[0077] (1) At room temperature, lithium hydroxide monohydrate and hydrogen peroxide in a certain molar ratio (1:1.2) are weighed, and lithium hydroxide monohydrate is added to hydrogen peroxide (hydrogen peroxide) for a synthesis reaction. The synthesis reaction is first carried out under low temperature conditions of less than 45°C with a stirring reaction speed of 500 rpm and a stirring time of 2 hours, and then heated to 95°C for a stirring reaction under high temperature conditions with a stirring speed of 500 rpm and a stirring time of 4 hours. After the reaction is completed, the solid-liquid separation is carried out to obtain lithium peroxide with a low water content.

[0078] (2) The low-water-content lithium peroxide is placed in a PECVD vacuum furnace and vacuum dried at 95° C. to obtain lithium peroxide.

[0079] (3) After the above reaction is completed, the lithium peroxide is heated to 800°C in a PECVD vacuum furnace, kept at this temperature for 5 hours, and then naturally cooled to room temperature to obtain a battery-grade lithium oxide powder product.

[0080] (4) After the above reaction is completed, a plasma enhanced chemical vapor deposition program is set up in a PECVD vacuum furnace: the temperature is raised from room temperature to 500°C at a rate of 2°C / min, high-purity acetylene gas is introduced into the atmosphere furnace, and the temperature is kept at 500°C for 1 hour and then naturally cooled to room temperature. Under this program, lithium oxide is carbon-coated, and then sieved and demagnetized to obtain lithium oxide-1. The residual alkali content of the finished product is tested. The residual alkali content of the finished product is shown in Table 1. The finished product is characterized by XRD, and the results are as follows Figure 3 .

[0081] Comparative Example 3

[0082] Synthesis of phase-pure lithium nitride.

[0083] (1) Place the lithium sheet in a PECVD vacuum atmosphere furnace, introduce high-purity nitrogen, heat to 250°C and keep warm for 20 hours, then naturally cool to room temperature to obtain a lithium nitride powder product.

[0084] (2) After the above reaction is completed, a plasma enhanced chemical vapor deposition program is set up in a PECVD vacuum furnace: the temperature is raised from room temperature to 500°C at a rate of 2°C / min, high-purity acetylene gas is introduced into the atmosphere furnace, and the temperature is kept at 500°C for 1 hour and then naturally cooled to room temperature. Under this program, lithium nitride is carbon-coated, and then lithium nitride-1 is obtained by screening and demagnetization. The residual alkali content of the finished product is tested. The residual alkali content of the finished product is shown in Table 1. The finished product is characterized by XRD, and the results are as follows Figure 4 .

[0085] Test Example 1

[0086] (1) 4 g of the lithium supplement material prepared in the above-mentioned embodiments and comparative examples, 0.5 g of conductive carbon black and 0.5 g of polyvinylidene fluoride were added to 10 ml of NMP solution and stirred (rotation speed 1000 rpm) for 10 min to prepare a slurry.

[0087] (2) The slurry is coated on an aluminum foil and baked at 100° C. in vacuum for 8 h to obtain a positive electrode sheet 1.

[0088] (3) The positive electrode sheet 1 is cut into round pieces with a diameter of 14 mm to obtain the positive electrode sheet, and then assembled into a CR2032 button battery in the order of positive electrode sheet-diaphragm-lithium foil.

[0089] The button cell assembled above was subjected to a performance test, and the test method was as follows.

[0090] The operating voltage range of the assembled button cell was set to 2.5V~4.2V. It was charged to 4.2V at a constant current of 0.05C and then charged to 0.01C. Then, it was discharged to 2V at a current of 0.05C. The first cycle charging specific capacity and first efficiency of the lithium-rich lithium ferrite material prepared in the above-mentioned embodiments and comparative examples at a rate of 0.05C were tested. The results are shown in Table 2.

[0091] Test Example 2

[0092] The materials prepared in the examples and comparative examples were placed in a constant temperature and humidity chamber with a temperature of (25±3)°C and a relative humidity of 20% RH for 30 minutes, and then the samples were taken out and subjected to a buckle electrochemical performance test according to Test Example 1. The results are shown in Table 3.

[0093]

[0094]

[0095]

[0096] It can be seen from the results in Table 1 that the residual alkali content of the composite binary lithium material-7 in comparative example 1 which has not been subjected to carbon coating treatment is high; the residual alkali content of comparative example 2, comparative example 3 and each embodiment of the present invention (i.e., the composite binary lithium material subjected to carbon coating treatment) which has been subjected to carbon coating treatment is lower; this indicates that the carbon coating treatment can effectively prevent CO2 and H2O in the air from reacting with the material to generate residual alkali, thereby significantly reducing its residual alkali content.

[0097] It can be seen from the results in Table 2 that the composite binary lithium material of comparative example 1 that has not been carbon-coated has the lowest first-cycle charge capacity, because the conductivity of the material is relatively low and the air stability is poor when not coated, and the specific capacity of the material cannot be fully utilized; although the lithium oxide-1 treated with carbon coating in comparative example 2 and the lithium nitride-1 treated with carbon coating in comparative example 3 show a higher charge capacity, since the intrinsic performance defects of each material have not been resolved, their "theoretical" charge capacity under the test conditions is far from being fully utilized; and compared with the comparative example, on the whole, the first-cycle charge capacity of each embodiment of the present invention (i.e., the composite binary lithium material coated with carbon) is the highest; this shows that the composite use of lithium oxide and lithium nitride can reduce the theoretical decomposition potential of lithium oxide, and coating the composite material can reduce its sensitivity to moisture and carbon dioxide in the air, thereby greatly improving the first charge capacity of the composite binary lithium material.

[0098] It can be seen from the results in Table 3 that after the carbon coating process, the air stability of each embodiment is significantly improved compared with the comparative example 1, and the gram-specific capacity of the comparative example 1 sample which has not been carbon coated decreases significantly after being placed in a certain humidity environment.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a composite binary lithium supplement material, characterized in that: The following steps are involved: 1) mixing a lithium source and a carbon source, and reacting them in a PECVD vacuum atmosphere device at a first temperature to obtain a composite A; 2) lowering the temperature from the first temperature to a second temperature, introducing nitrogen gas to allow the compound A to react with the nitrogen gas to obtain a compound B; 3) the temperature is raised from the second temperature to a third temperature, and a gas is introduced to coat the composite B with a carbon layer to obtain a composite binary lithium supplement material; In step 1), the carbon source is lithium carbide and / or carbon black; the lithium source is lithium oxide and / or lithium hydroxide, and the molar ratio of lithium in the lithium source to carbon in the carbon source is (0.8-0.2): (0.2-0.8); the heating program of the first temperature is: heating to 500-600°C at a heating rate of 2-10°C / min, keeping warm for 2-5h, and then heating to 800-1000°C, keeping warm for 1-5h; in step 2), The second temperature is 200~400℃, the cooling rate is 2~10℃ / min, and the insulation time is 5~30h; in step 3), during the carbon layer coating process, the third temperature is 400~700℃, and the reaction time is 0.5~5h; in step 3), during the carbon layer coating process, the gas is selected from one or more of high-purity methane, ethane, propane, butane, ethylene, propylene, butene, pentene, acetylene, propyne and butyne.

2. The method for preparing the composite binary lithium supplement material according to claim 1, characterized in that: In step 1), the vacuum atmosphere pressure is 10~100 Pa.

3. The method for preparing the composite binary lithium supplement material according to claim 2, characterized in that: In step 1), the vacuum atmosphere pressure is 10~50Pa.

4. The method for preparing the composite binary lithium supplement material according to claim 1, characterized in that: In step 1), the heating program of the first temperature is: heating to 550-600°C at a heating rate of 2-5°C / min, keeping the temperature for 2-3 hours, and then heating to 900-1000°C, keeping the temperature for 2-5 hours.

5. The method for preparing the composite binary lithium supplement material according to claim 1, characterized in that: In step 2), the second temperature is 200-300°C, the cooling rate is 2-5°C / min, and the holding time is 10-25h.

6. The method for preparing the composite binary lithium supplement material according to claim 1, characterized in that: In step 3), during the carbon layer coating process, the plasma chemical vapor deposition procedure is: after the temperature is raised from the second temperature to the third temperature at a rate of 1-3°C / min, the gas is introduced into the PECVD vacuum atmosphere equipment, the temperature is kept at the third temperature, and then naturally cooled to obtain a carbon layer coated composite binary lithium supplement material.

7. The method for preparing the composite binary lithium supplement material according to claim 1, characterized in that: In step 3), during the carbon layer coating process, the carbon coating amount on the surface of the composite binary lithium supplementing material accounts for 0.5% to 5%.

8. The composite binary lithium-supplementing material prepared by the method for preparing the composite binary lithium-supplementing material according to any one of claims 1 to 7, characterized in that: The chemical formula of the composite binary lithium supplement material is: xLi2O-yLi3N-zC@C; x+y+z=1, 0.1≤x≤0.9, 0.1≤y≤0.9, 0.01≤z≤0.2; The surface of the composite binary lithium supplement material is coated with a carbon coating layer of a conductive carbon material, and the thickness of the carbon coating layer is 0.5-200 nm.

Citation Information

Patent Citations

  • Hard carbon negative electrode composite material and preparation method and application thereof

    CN113184827A

  • Binary lithium supplement additive and preparation method and application thereof

    CN115692696A

  • Preparation method and application of lithium nitride

    CN116654879A